Analisis Faktor yang Mempengaruhi Keputusan Pembelian, Studi Empirik Kosmetika Wardah - Zulfha Asmar Nurlia (Journal of Economics and Business Aseanomics (JEBA), 2022)
This study aims to analyze and describe the factors that influence purchasing decisions through brand image as an intervening variable. The survey method was used by taking a sample using an incidental technique of 200 people. The data processing technique uses a questionnaire (google form) and this research is a Structural Equation Modeling (SEM), with data analysis using the SPSS and SmartPLS application.The study indicates that Muslim women aged 18-45 years have a high enough interest to look attractive by using lipstick and skincare for activities from home during the pandemic. This supports the analysis showing that the halal label, brand ambassador, and product quality influence purchasing decisions. However, the brand image does not mediate the effect of the halal label, brand ambassador, and product quality on purchasing decisions.